A SHORT REVIEW ON APSMARA W.S.R. TO EPILIPSY - R Gulhane, Amit; B Rathi, Renu; S Chavan, Ganesh (International Journal of Research -GRANTHAALAYAH, 2019)
Today’s modern era, different types of stress, mental depression, night duties, insomnia, internet working, web searching, playing games on mobile lack of proper diet etc. All this leads prevalence of mental diseases day by day. Epilepsy is a mental disorder in which the central nervous system characterized by periodic loss of consciousness with or without convulsions associated with abnormal electrical activity in the brain. In some cases, it is due to brain damage, but in most cases the cause is unknown. In Ayurveda all psychiatric disorder is described under the heading of mansika vyadhi Apsmara is one of them. “Apsamarm punah: smrutibudhi satwasamplawat bibhasachestam awastitakam tama: praveshamachkaste”- it’s the one-line unique identity of Apsmara. It is the transient appearance of unconsciousness with loath some expression due to derangement of memory, intelligence and mind. The present article is an attempt to highlighting on details of Apsmara with co-relating with Epilepsy.